Kontektualisasi Aliran Filsafat Prgresivisme Dalam Pandangan Pendidikan Islam di Indonesia - M. Yunus Abu bakar; Nawal Zahwa Dzakiyyah; Inayah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article discusses the philosophical schools of progressivism which cover various fields. The application of progressivism in learning based on the philosophy of progressivism in the concept of freedom to learn is so that readers can understand examples of the application of progressivism which are explained in detail in the educational curriculum in Indonesia. The method used in this article is a qualitative method using a library research approach. In this phase, the researcher tried to select data (books) related to the flow of progressivism and its figures. From the results of our research, we found that progressivism is a school of educational philosophy that supports educational change and progress as a response to changing times. Some of the figures in it are William James, John Dewey, and Hans Vaihinger. The goal of Progressivism is to develop students who can think practically and use their experience to solve problems effectively in an increasingly developing and advanced environment. Educators only act as motivators, guides, or instructors for students. The curriculum used is flexible, free, open and does not indoctrinate students. Indonesia is one of the countries that develops a curriculum to keep up with the times and compete with international education.